Dose-resposta da imersão em água fria na recuperação do sistema nervoso autônomo pós-exercício - Almeida, Aline Castilho de [UNESP] (2014)
Cold water immersion (CWI) has been used substantially in post-exercise recovery. However, there are still gaps in knowledge about its use in the recovery of the autonomic nervous system, especially in the question dose-response. Objectives: To analyze and compare the effects of the CWI during post-exercise recovery, from different times and temperatures on heart rate variability (HRV) indices. Method: 96 participants were randomly divided into five groups (GC: control; G1: 5' at 9±1°C; G2: 5' at 14±1°C; G3: 15' at 9±1°C; G4: 15' at 14±1°C), performed a program of jumps and the Wingate test and were immediately immersed in a tank with cold water until the height of the anterior superior iliac spine, according to each group characteristics. Analysis were performed before (baseline), during recovery intervention (intervention) and 20, 30, 40, 50 and 60 minutes after exercise (T20, T30, T40, T50 and T60). The mean RR, SDNN, RMSSD, VLF, LF, HF, SD1 and SD2 HRV indices were evaluated. Data were analyzed using the Kolmogorov-Smirnov test to check normality...